Positive electrode for lithium ion secondary battery and lithium ion secondary battery
Patent Information
- Application Number
- JP2021204583
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-16
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-12-16
AI Technical Summary
【0008】 本開示の正極をリチウムイオン二次電池に適用した場合、当該電池が優れたサイクル特性を有するものになり易い。
Smart Images

Figure 0007643320000004 
Figure 0007643320000005 
Figure 0007643320000006
Abstract
Description
[Technical field]
[0001] The present application discloses a positive electrode for a lithium ion secondary battery and a lithium ion secondary battery. [Background technology]
[0002] Patent Document 1 discloses a positive electrode active material having a composition represented by LiMnO2 and having a zigzag layer structure as a matrix structure and an α-NaFeO2 type layer structure as a domain. In Patent Document 1, the positive electrode active material is applied to a nonaqueous electrolyte battery. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-153564 A Summary of the Invention [Problem to be solved by the invention]
[0004] According to the findings of the present inventors, when the positive electrode active material disclosed in Patent Document 1 is applied to a non-aqueous electrolyte battery, the cycle characteristics of the battery are likely to deteriorate. [Means for solving the problem]
[0005] As one of the means for solving the above problems, the present application provides: A sulfide solid electrolyte; The positive electrode active material is Li x Mn y and having a composition represented by the formula: α-NaFeO2 (0.95≦x≦1.05 and 0.95≦y≦1.05), and having a zigzag layered structure as a matrix structure and an α-NaFeO2 type layered structure as a domain. A positive electrode for a lithium ion secondary battery, Disclose.
[0006] In the positive electrode for a lithium ion secondary battery of the present disclosure, a protective layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material.
[0007] As one of the means for solving the above problems, the present application provides: The positive electrode for a lithium ion secondary battery according to the present disclosure, A sulfide solid electrolyte layer; A negative electrode; A lithium ion secondary battery having Disclose. Effect of the Invention
[0008] When the positive electrode of the present disclosure is applied to a lithium ion secondary battery, the battery is likely to have excellent cycle characteristics. [Brief description of the drawings]
[0009] [Figure 1] 1 illustrates a schematic configuration of a lithium ion secondary battery. [Diagram 2] 4 shows the X-ray diffraction peaks of the first intermediate material, the second intermediate material, and the positive electrode active material A. [Diagram 3] 2 shows charge / discharge curves of the lithium ion secondary batteries according to Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] 1. Positive electrodes for lithium-ion secondary batteries The positive electrode for a lithium ion secondary battery of the present disclosure comprises a sulfide solid electrolyte and a positive electrode active material, Li x Mn y The composition of the NaFeO2 alloy is represented by the formula: (x, y, and y)=0.95≦x≦1.05 and (y, 0.95≦y≦1.05), and the NaFeO2 alloy has a zigzag layered structure as a matrix structure and an α-NaFeO2 type layered structure as a domain.
[0011] 1.1 Sulfide solid electrolyte The sulfide solid electrolyte can be any one used as a solid electrolyte for lithium ion secondary batteries. The sulfide solid electrolyte contains at least Li and S as constituent elements. In particular, sulfide solid electrolytes containing Li, S, and P as constituent elements have high performance. Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Si2S-P2S5, Li2S-P2S5-LiI-LiBr, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5-GeS2, and the like. The sulfide solid electrolyte may be amorphous or crystalline. The sulfide solid electrolyte may be, for example, particulate. The sulfide solid electrolyte may be used alone or in combination of two or more kinds.
[0012] 1.2 Cathode active material The positive electrode of the present disclosure includes, together with the sulfide solid electrolyte, a positive electrode active material having the following composition and crystal structure. When such a positive electrode is applied to a lithium ion secondary battery, the lithium ion secondary battery is likely to have excellent cycle characteristics.
[0013] 1.2.1 Composition The positive electrode active material is Li x Mn y O2 (0.95≦x≦1.05 and 0.95≦y≦1.05). With such a composition, a high capacity is easily ensured and the crystal structure described below is easily maintained. x is 0.95 or more, and may be 0.96 or more, 0.97 or more, 0.98 or more, or 0.99 or more, and may be 1.05 or less, 1.04 or less, 1.03 or less, 1.02 or less, or 1.01 or less. In addition, y is 0.95 or more, and may be 0.96 or more, 0.97 or more, 0.98 or more, or 0.99 or more, and may be 1.05 or less, 1.04 or less, 1.03 or less, 1.02 or less, or 1.01 or less.
[0014] 1.2.2 Crystal structure The positive electrode active material has a zigzag layered structure as a matrix structure and an α-NaFeO2 type layered structure as a domain. As disclosed in Patent Document 1, the zigzag layered structure is a crystal structure in which layers in the α-NaFeO2 type layered structure grow alternately up and down in a regular manner to form a zigzag layered structure. The zigzag layered structure can be composed of orthorhombic lithium manganate (e.g., o-LiMnO2). On the other hand, the α-NaFeO2 type layered structure is also called a layered rock salt type structure, and is a cubic rock salt type structure. <111> In the direction, a transition metal (manganese in the positive electrode active material of the present disclosure) and lithium are regularly arranged to form a two-dimensional plane. A positive electrode active material having such a crystal structure can be obtained, for example, by subjecting an intermediate material having a zigzag layered structure to mechanical milling and heat treatment to change a part of the structure, as described later, to generate a domain of an α-NaFeO2 type layered structure.
[0015] The positive electrode active material having the above-mentioned matrix structure and domain may be one in which peaks derived from the (010), (200) and (021) planes of orthorhombic lithium manganate are confirmed in an X-ray diffraction pattern using CuKα as a radiation source, or one in which peaks derived from the (110) and (210) planes of orthorhombic lithium manganate are not substantially confirmed. For example, in the X-ray diffraction pattern, the diffraction peak intensity I derived from the (021) plane of orthorhombic lithium manganate may be 021 Diffraction peak intensity I originating from the (110) plane of orthorhombic lithium manganate 110 The ratio (I 110 / I 021 The ratio (I 110 / I 021 ) is 0.2 or less, the capacity of the positive electrode active material is likely to become even greater.
[0016] 1.2.3 Shape The positive electrode active material may have the above composition and crystal structure, and other configurations are not particularly limited. The shape of the positive electrode active material may be, for example, particulate or thin film, and may be selected appropriately according to the shape of the battery. When the positive electrode active material is particulate, the particles may be solid particles, hollow particles, or particles having voids. The particles of the positive electrode active material may be primary particles, or secondary particles formed by agglomeration of a plurality of primary particles. The average particle diameter (D50) of the particles of the positive electrode active material may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. The average particle diameter D50 in the present application is the particle diameter (median diameter) at an integrated value of 50% in the volume-based particle size distribution obtained by a laser diffraction / scattering method.
[0017] 1.2.4 Protective layer A protective layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material. This makes it easier to suppress the reaction between the positive electrode active material and the sulfide solid electrolyte. Examples of Li-ion conductive oxides include Li3BO3, LiBO2, Li2CO3, LiAlO2, Li4SiO4, Li2SiO3, Li3PO4, Li2SO4, Li2TiO3, and Li4Ti5O 12 , Li2Ti2O5, Li2ZrO3, LiNbO3, Li2MoO4, and Li2WO4. The Li ion conductive oxide may have some elements substituted with doping elements such as P and B. The coverage (area ratio) of the protective layer may be, for example, 70% or more, 80% or more, or 90% or more. The thickness of the protective layer may be, for example, 0.1 nm or more or 1 nm or more, and may be 100 nm or less, or 20 nm or less.
[0018] 1.2.5 Manufacturing method of positive electrode active material The above-mentioned positive electrode active material can be produced, for example, by the following method. That is, the method for producing a positive electrode active material according to one embodiment includes the following steps: Step S1: preparing a first intermediate material containing Li, Mn, and O as constituent elements and having a zigzag layered structure; Step S2: subjecting the first intermediate material to dry mechanical milling to prepare a second intermediate material containing Li, Mn, and O as constituent elements and having a disordered rock-salt structure; and Step S3: The second intermediate material is fired to form Li x Mn y To obtain a positive electrode active material having a composition represented by the formula: NaFeO2 (0.95≦x≦1.05 and 0.95≦y≦1.05) and having a zigzag layered structure as a matrix structure and an α-NaFeO2 type layered structure as a domain; It may include.
[0019] (1) Process S1 In step S1, a first intermediate substance is prepared, which contains Li, Mn, and O as constituent elements and has a zigzag layer structure. The first intermediate substance can be prepared, for example, by forming a mixture of a Li source and a Mn source into a desired shape and then firing the formed shape.
[0020] Examples of the Li source constituting the mixture include Li2CO3. Examples of the Mn source include Mn2O3 and MnCO3. Alternatively, other raw materials than those mentioned above may be used as the raw materials constituting the mixture, or a compound (composite oxide, etc.) that serves as both the Li source and the Mn source may be used. The composition ratio of Li and Mn contained in the mixture may be appropriately determined according to the composition ratio of the positive electrode active material, which is the final product. The mixture may be adjusted so that Li is contained in excess. This allows the shortage of Li to be compensated for even if Li volatilizes during the firing in step S1 or Li is consumed by a side reaction in step S2 or later described later. That is, the desired composition is easily obtained in the positive electrode active material, which is the final product.
[0021] The method of mixing the Li source and the Mn source is not particularly limited. The Li source and the Mn source can be mixed uniformly, for example, by wet mechanical milling using a solvent. As the solvent, for example, an organic solvent such as ethanol can be used. The wet mechanical milling can be performed by a mechanical mixing means such as a planetary ball mill. The mixing conditions (mixing time, rotation speed, number of repetitions, etc.) in the wet mechanical milling are not particularly limited, and the conditions may be such that the Li source and the Mn source are mixed uniformly to such an extent that the desired zigzag layered structure can be formed after firing as described below.
[0022] The mixture may be molded into pellets or the like before firing. The size and shape of the molded body are not particularly limited.
[0023] The mixture or the molded body is fired to obtain a first intermediate material having a zigzag layer structure. The firing atmosphere is not particularly limited, and may be, for example, an oxygen-containing atmosphere such as an air atmosphere or an air atmosphere, or an inert gas atmosphere such as an Ar atmosphere. In particular, the first intermediate material is easily obtained when the atmosphere is an inert gas atmosphere. The firing temperature is not particularly limited as long as the zigzag layer structure is obtained. For example, it may be 800°C or higher or 850°C or higher, and may be 1000°C or lower or 950°C or lower. The firing time (holding time at the firing temperature) is also not particularly limited, and may be, for example, 5 hours or more, 7 hours or more, 10 hours or more, or 12 hours or more, and may be 100 hours or less, 50 hours or less, or 20 hours or less.
[0024] (2) Process S2 In step S2, the first intermediate substance is subjected to dry mechanical milling to produce a second intermediate substance containing Li, Mn, and O as constituent elements and having an irregular rock-salt structure. That is, by subjecting the first intermediate substance to dry mechanical milling substantially without using a solvent, the zigzag layer structure of the first intermediate substance is changed to obtain a second intermediate substance having an irregular rock-salt structure.
[0025] Dry mechanical milling can be carried out by mechanical mixing means such as a planetary ball mill. The conditions of dry mechanical milling (mixing time, rotation speed, number of repetitions, etc.) are not particularly limited. For example, in the case of using a planetary ball mill, the rotation speed may be 500 to 700 rpm, the rotation time may be 10 to 20 minutes, and the rest time may be 1 to 5 minutes. Rotation and rest may be repeated multiple times, and further, one set of repetition of rotation and rest may be repeated multiple times. By adjusting the conditions of dry mechanical milling, for example, the crystallite size of the positive electrode active material may be controlled.
[0026] (3) Process S3 In step S3, the second intermediate material is fired to obtain Li x Mn y A positive electrode active material having a composition represented by O2 (0.95≦x≦1.05 and 0.95≦y≦1.05) and having a zigzag layered structure as a matrix structure and an α-NaFeO2 type layered structure as a domain is obtained.
[0027] The firing atmosphere is not particularly limited, and may be, for example, an oxygen-containing atmosphere such as an air atmosphere or an air atmosphere, or an inert gas atmosphere such as an Ar atmosphere. In particular, the desired positive electrode active material is easily obtained when the atmosphere is an inert gas atmosphere. The firing temperature is not particularly limited as long as a zigzag layer structure as a parent structure and an α-NaFeO2 type layer structure as a domain are obtained. For example, it may be 600°C or higher or 650°C or higher, and 800°C or lower or 750°C or lower. If the firing temperature is too high, the α-NaFeO2 type layer structure tends to be reduced. The firing time (holding time at the firing temperature) is also not particularly limited, and may be, for example, 30 minutes or more, 1 hour or more, or 2 hours or more, and 10 hours or less, 5 hours or less, or 3 hours or less.
[0028] The second intermediate material may be molded into pellets or the like before firing. The size and shape of the molded body are not particularly limited.
[0029] (4) Supplementary information In the above manufacturing method, the composition ratio of Li and Mn may vary or may be substantially the same from the above mixture through the first intermediate material and the second intermediate material to the positive electrode active material. In the above description, the intermediate material and the like are produced by a solid-phase reaction method, but the method for producing the intermediate material and the like is not limited to this. In the above description, the first intermediate material is subjected to dry mechanical milling, but there is also room for other methods to be adopted as a method for obtaining the second intermediate material having an irregular rock salt structure. However, as far as the inventor has confirmed, by producing the first intermediate material having a zigzag layer structure and then subjecting the first intermediate material to dry mechanical milling, the irregular rock salt structure can be stably and easily obtained, and the positive electrode active material having the desired matrix structure and domain can be easily obtained through the subsequent firing.
[0030] 1.3 Other configurations for the positive electrode As described above, the positive electrode for lithium ion secondary battery of the present disclosure is characterized in that it contains a sulfide solid electrolyte and a predetermined positive electrode active material, and other configurations are not particularly limited. Figure 1 shows a schematic configuration of a positive electrode 10 according to one embodiment. As shown in Figure 1, the positive electrode 10 may include a positive electrode active material layer 11 and a positive electrode current collector 12, and the positive electrode active material layer 11 may contain the above-mentioned sulfide solid electrolyte and positive electrode active material.
[0031] 1.3.1 Cathode active material layer The positive electrode active material layer 11 includes at least the sulfide solid electrolyte and the positive electrode active material, and may further include other active materials, other electrolytes, conductive assistants, binders, and the like. The positive electrode active material layer 11 may also include various additives other than these. The content of each of the positive electrode active material, electrolyte, conductive assistant, binder, and the like in the positive electrode active material layer 11 may be appropriately determined according to the intended battery performance. For example, the content of the positive electrode active material may be 40% by mass or more, 50% by mass or more, or 60% by mass or more, and may be 100% by mass or less, or 90% by mass or less, with the entire positive electrode active material layer 11 (total solid content) being 100% by mass. The shape of the positive electrode active material layer 11 is not particularly limited, and may be, for example, a sheet-like positive electrode active material layer 11 having a substantially flat surface. The thickness of the positive electrode active material layer 11 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.
[0032] The positive electrode active material layer 11 may contain only the positive electrode active material of the present disclosure as the positive electrode active material. Alternatively, the positive electrode active material layer 11 may contain, in addition to the positive electrode active material of the present disclosure, a different type of positive electrode active material (another positive electrode active material). From the viewpoint of further enhancing the effect of the technology of the present disclosure, the content of the other positive electrode active material in the positive electrode active material layer 11 may be small. For example, the positive electrode active material of the present disclosure may account for 50 mass% or more, 60 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, 95 mass% or more, or 99 mass% or more of the total positive electrode active material contained in the positive electrode active material layer 11.
[0033] The positive electrode active material layer 11 may contain only the sulfide solid electrolyte as an electrolyte. Alternatively, the positive electrode active material layer 11 may contain, in addition to the sulfide solid electrolyte, a different type of solid electrolyte (another solid electrolyte). From the viewpoint of further enhancing the effect of the technology of the present disclosure, the content of the other solid electrolyte in the positive electrode active material layer 11 may be small. For example, the sulfide solid electrolyte may occupy 50 mass% or more, 60 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, 95 mass% or more, or 99 mass% or more of the total solid electrolyte contained in the positive electrode active material layer 11. The positive electrode active material layer 11 may also contain a liquid electrolyte in addition to the sulfide solid electrolyte. As described later, although the liquid electrolyte may decompose at a high potential, in the positive electrode of the present disclosure, high ion conductivity can be ensured by the sulfide solid electrolyte even if the liquid electrolyte decomposes. An example of an electrolyte other than the sulfide solid electrolyte is as follows. That is, the solid electrolyte other than the sulfide solid electrolyte may be an inorganic solid electrolyte or an organic polymer electrolyte. In particular, the inorganic solid electrolyte has excellent ion conductivity and heat resistance. Examples of the inorganic solid electrolyte other than the sulfide solid electrolyte include lithium lanthanum zirconate, LiPON, Li 1+X Al X Ge 2-X Examples of the oxide solid electrolyte include (PO4)3, Li-SiO-based glass, and Li-Al-SO-based glass. The liquid electrolyte may contain, for example, lithium ions as carrier ions. The liquid electrolyte may be a lithium salt dissolved in a solvent.
[0034] Examples of the conductive assistant that may be included in the positive electrode active material layer 11 include carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF); and metal materials such as nickel, aluminum, and stainless steel. The conductive assistant may be, for example, particulate or fibrous, and its size is not particularly limited. Only one type of conductive assistant may be used alone, or two or more types may be used in combination.
[0035] Examples of binders that can be included in the positive electrode active material layer 11 include butadiene rubber (BR)-based binders, butylene rubber (IIR)-based binders, acrylate butadiene rubber (ABR)-based binders, styrene butadiene rubber (SBR)-based binders, polyvinylidene fluoride (PVdF)-based binders, polytetrafluoroethylene (PTFE)-based binders, polyimide (PI)-based binders, etc. Only one type of binder may be used alone, or two or more types may be used in combination.
[0036] 1.3.2 Positive electrode current collector As shown in FIG. 1, the positive electrode 10 may include a positive electrode collector 12 in contact with the positive electrode active material layer 11. The positive electrode collector 12 may be any of those commonly used as a positive electrode collector for a battery. The positive electrode collector 12 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, or the like. The positive electrode collector 12 may be made of a metal foil or a metal mesh. In particular, a metal foil is excellent in terms of ease of handling. The positive electrode collector 12 may be made of a plurality of foils. Examples of metals constituting the positive electrode collector 12 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, and the like. In particular, from the viewpoint of ensuring oxidation resistance, the positive electrode collector 12 may contain Al. The positive electrode collector 12 may have some kind of coating layer on its surface for the purpose of adjusting resistance, or the like. The positive electrode current collector 12 may be a metal foil or a substrate plated or vapor-deposited with the above metal. When the positive electrode current collector 12 is made of a plurality of metal foils, some layer may be present between the plurality of metal foils. The thickness of the positive electrode current collector 12 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.
[0037] 1.3.3 Other In addition to the above configuration, the positive electrode 10 may have a general configuration as a battery positive electrode. For example, a tab, a terminal, etc. The positive electrode 10 can be manufactured by a known method except for using the above sulfide solid electrolyte and the positive electrode active material. For example, the positive electrode active material layer 11 can be easily formed by forming a positive electrode mixture containing at least the above sulfide solid electrolyte and the positive electrode active material in a dry or wet manner. The positive electrode active material layer 11 may be formed together with the positive electrode current collector 12 or may be formed separately from the positive electrode current collector 12.
[0038] 4. Lithium-ion secondary battery The technology of the present disclosure also has an aspect as a lithium ion secondary battery. That is, the lithium ion secondary battery of the present disclosure has the above-mentioned lithium ion secondary battery positive electrode of the present disclosure, a sulfide solid electrolyte layer, and a negative electrode. The lithium ion secondary battery of the present disclosure is likely to have better cycle characteristics by combining the above-mentioned positive electrode of the present disclosure with the sulfide solid electrolyte layer. The specific configuration of the lithium ion secondary battery of the present disclosure is not particularly limited. For example, as shown in FIG. 1, a lithium ion secondary battery 100 according to one embodiment may have a positive electrode 10, a sulfide solid electrolyte layer 20, and a negative electrode 30. The positive electrode 10 is as described above.
[0039] 4.1 Sulfide solid electrolyte layer The sulfide solid electrolyte layer 20 includes at least a sulfide solid electrolyte. The sulfide solid electrolyte layer 20 may further include a binder or the like. The sulfide solid electrolyte layer 20 may be made of a solid, or may include a liquid in part. The sulfide solid electrolyte layer 20 may include other solid electrolytes or liquid electrolytes together with the sulfide solid electrolyte. Alternatively, the sulfide solid electrolyte layer 20 may not include a liquid electrolyte. Furthermore, the sulfide solid electrolyte layer 20 may include various additives. Specific examples of the sulfide solid electrolyte, other solid electrolytes, liquid electrolytes, and binders are as described above. That is, various electrolytes and binders that can be included in the sulfide solid electrolyte layer 20 may be appropriately selected from those exemplified as those that can be included in the positive electrode 10. The content of the sulfide solid electrolyte and binders in the sulfide solid electrolyte layer 20 is not particularly limited. The thickness of the sulfide solid electrolyte layer 20 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.
[0040] 4.2 Negative electrode The form of the negative electrode is not particularly limited. For example, as shown in FIG.
[0041] 4.2.1 Negative electrode active material layer The negative electrode active material layer 31 includes at least a negative electrode active material, and may further include an electrolyte, a conductive assistant, a binder, and the like. The negative electrode active material layer 31 may further include various additives. The contents of the negative electrode active material, electrolyte, conductive assistant, binder, and the like in the negative electrode active material layer 31 may be appropriately determined according to the intended battery performance. For example, the content of the negative electrode active material may be 40 mass% or more, 50 mass% or more, or 60 mass% or more, and may be 100 mass% or less, or 90 mass% or less, with the entire negative electrode active material layer 31 (total solid content) being 100 mass%. The shape of the negative electrode active material layer 31 is not particularly limited, and may be, for example, a sheet-like negative electrode active material layer having a substantially flat surface. The thickness of the negative electrode active material layer 31 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.
[0042] As the negative electrode active material, various substances can be used that have a potential (charge / discharge potential) at which lithium ions are inserted and removed that is lower than the above-mentioned positive electrode active material. For example, silicon-based active materials such as Si, Si alloys, and silicon oxide; carbon-based active materials such as graphite and hard carbon; various oxide-based active materials such as lithium titanate; metallic lithium, lithium alloys, and the like can be used. Only one type of negative electrode active material may be used alone, or two or more types may be used in combination.
[0043] The shape of the negative electrode active material may be any shape that is common for a negative electrode active material of a battery. For example, the negative electrode active material may be in a particulate form. The negative electrode active material particles may be primary particles or secondary particles formed by agglomeration of a plurality of primary particles. The average particle diameter (D50) of the negative electrode active material particles may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. Alternatively, the negative electrode active material may be in a sheet form (foil form, film form) such as metallic lithium foil. That is, the negative electrode active material layer 31 may be made of a sheet of the negative electrode active material.
[0044] Examples of the electrolyte that can be contained in the negative electrode active material layer 31 include the above-mentioned solid electrolyte and liquid electrolyte. Examples of the conductive assistant that can be contained in the negative electrode active material layer 31 include the above-mentioned carbon material and the above-mentioned metal material. The binder that can be contained in the negative electrode active material layer 31 may be appropriately selected from, for example, those exemplified as those that can be contained in the above-mentioned positive electrode active material layer 11.
[0045] 4.2.2 Negative electrode current collector As shown in FIG. 2, the negative electrode 30 may include a negative electrode current collector 32 in contact with the negative electrode active material layer 31. The negative electrode current collector 32 may be any of those commonly used as a negative electrode current collector for a battery. The negative electrode current collector 32 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, or the like. The negative electrode current collector 32 may be a metal foil or a metal mesh, or may be a carbon sheet. In particular, a metal foil is excellent in terms of ease of handling. The negative electrode current collector 32 may be made of a plurality of foils or sheets. Examples of metals constituting the negative electrode current collector 32 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, and the like. In particular, from the viewpoint of ensuring reduction resistance and being difficult to alloy with lithium, the negative electrode current collector 32 may contain at least one metal selected from Cu, Ni, and stainless steel. The negative electrode current collector 32 may have some kind of coating layer on its surface for the purpose of adjusting the resistance or the like. The negative electrode current collector 32 may be a metal foil or a base material on which the above metal is plated or vapor-deposited. When the negative electrode current collector 32 is made of a plurality of metal foils, some kind of layer may be present between the plurality of metal foils. The thickness of the negative electrode current collector 32 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less. In addition to the above configuration, the negative electrode 30 may have a general configuration as a battery negative electrode. For example, a tab, a terminal, or the like.
[0046] 4.3 Other The lithium ion secondary battery 100 may have the above-mentioned components housed inside an exterior body. Any known exterior body for a battery can be used as the exterior body. A plurality of batteries 100 may be electrically connected and stacked in any manner to form an assembled battery. In this case, the assembled battery may be housed inside a known battery case. The lithium ion secondary battery 100 may also have other obvious components such as necessary terminals. The shape of the lithium ion secondary battery 100 may be, for example, a coin type, a laminate type, a cylindrical type, a square type, or the like.
[0047] The lithium ion secondary battery 100 can be manufactured by applying a known method. For example, a method for manufacturing the lithium ion secondary battery 100 includes stacking the above-mentioned positive electrode 10, sulfide solid electrolyte layer 20, and negative electrode 30. A specific example of a method for manufacturing the lithium ion secondary battery 100 is shown below. However, the method for manufacturing the lithium ion secondary battery 100 is not limited to the following method, and each layer may be formed by, for example, dry molding or the like. (1) The positive electrode active material constituting the positive electrode active material layer is dispersed in a solvent to obtain a positive electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used, and N-methylpyrrolidone (NMP) can also be used. The positive electrode layer slurry is applied to the surface of a positive electrode current collector using a doctor blade or the like, and then dried to form a positive electrode active material layer on the surface of the positive electrode current collector, which serves as a positive electrode. (2) The negative electrode active material constituting the negative electrode active material layer is dispersed in a solvent to obtain a negative electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used, and N-methylpyrrolidone (NMP) may be used. The negative electrode layer slurry is then applied to the surface of a negative electrode current collector using a doctor blade or the like, and then dried to form a negative electrode active material layer on the surface of the negative electrode current collector, forming a negative electrode. Alternatively, a metal foil that is a negative electrode active material may be used as it is as a negative electrode. (3) The layers are laminated so that the sulfide solid electrolyte layer is sandwiched between the negative electrode and the positive electrode to obtain a laminate having a negative electrode current collector, a negative electrode active material layer, a sulfide solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector in this order. Other members such as terminals are attached to the laminate as necessary. The sulfide solid electrolyte layer may be formed in advance, or may be formed together with the positive electrode and / or the negative electrode. (4) The laminate is housed in a battery case and sealed to form a lithium ion secondary battery. When each layer is impregnated with a liquid, the timing of impregnation is not particularly limited.
[0048] 5. Supplementary Information In the case of a lithium ion secondary battery using only a liquid electrolyte as an electrolyte as in Patent Document 1, when a positive electrode active material having the above composition and crystal structure is adopted, decomposition of the liquid electrolyte is easily promoted when the battery is operated at a high potential to fully exert the performance of the positive electrode active material. As a result, there is a risk that sufficient cycle characteristics cannot be obtained. In contrast, in the positive electrode for a lithium ion secondary battery of the present disclosure, the above positive electrode active material is used together with a sulfide solid electrolyte, thereby solving the problems with the liquid electrolyte. This is because the sulfide solid electrolyte is less likely to decompose even at a high potential compared to the liquid electrolyte.
[0049] In addition, the sulfide solid electrolyte and conventional positive electrode active materials (e.g., LiMn 1 / 3 Ni 1 / 3 Co 1 / 3In the case of combining a sulfide solid electrolyte with a cathode active material having a specific composition and crystal structure, such as O2, a resistor is likely to be generated between the sulfide solid electrolyte and the cathode active material, which is likely to cause deterioration of the cycle characteristics of the lithium ion secondary battery. In contrast, by combining a cathode active material having a specific composition and crystal structure with a sulfide solid electrolyte, as in the case of the cathode for lithium ion secondary battery of the present disclosure, the cycle characteristics of the lithium ion secondary battery are likely to be excellent. This is considered to be because the cathode active material having the above specific composition and crystal structure has low reactivity with the sulfide solid electrolyte at high potential, making it difficult for a resistor to be generated between the cathode active material and the sulfide solid electrolyte. As far as the present inventor has confirmed, such an effect is unique to the cathode active material having the above specific composition and crystal structure. EXAMPLES
[0050] The technology of the present disclosure will be described in more detail below with reference to examples, but the technology of the present disclosure is not limited to the following examples.
[0051] 1. Synthesis of positive electrode active material A 1.1 Preparation of the first intermediate MnCO3 was calcined at 700°C for 12 hours in an air atmosphere to obtain Mn2O3. Mn2O3 (1 mol) and Li2CO3 (1.03 mol, 3% excess) were weighed and mixed by wet ball milling (wet BM), a type of wet mechanical milling. The conditions for wet BM are as shown in Table 1 below. The mixture was then pelletized. The pellets were placed on a boat-shaped aluminum board, wrapped in Cu foil, and calcined at 900°C for 12 hours in an Ar atmosphere to obtain a first intermediate substance. From the X-ray diffraction peaks and elemental analysis, the first intermediate substance contained Li, Mn, and O as constituent elements and had a zigzag layered structure.
[0052] 1.2 Preparation of the second intermediate The second intermediate material was obtained by subjecting the first intermediate material to dry ball milling (dry BM), which is a type of dry mechanical milling. The conditions for dry BM are as shown in Table 1 below. For each set of dry BM, the powder on the wall of the ball mill pot was scraped off in a glove box. The second intermediate material contained Li, Mn, and O as constituent elements and had an irregular rock salt structure.
[0053] 1.3 Firing The second intermediate material was pelletized. The pellets were placed on a boat-shaped aluminum board, wrapped in Cu foil, and sintered in an Ar atmosphere at 700°C for 2 hours to obtain positive electrode active material A. From the X-ray diffraction peaks and elemental analysis, positive electrode active material A was found to contain Li x Mn y The composition was represented by the formula O2 (0.95≦x≦1.05 and 0.95≦y≦1.05), and the zigzag layered structure was the parent structure, and the α-NaFeO2 type layered structure was the domain.
[0054] [Table 1]
[0055] FIG. 2 shows the X-ray diffraction peaks of the first intermediate material before dry mechanical milling, the X-ray diffraction peaks of the second intermediate material after dry mechanical milling, and the X-ray diffraction peaks of the positive electrode active material A after final sintering. As shown in FIG. 2, for the first intermediate material, peaks derived from the (010), (110), (200), (210), and (021) planes of orthorhombic LiMnO2 are confirmed. For the second intermediate material, the crystal structure is changed by mechanical milling, and a broad peak derived from an irregular rock salt structure is confirmed. For the positive electrode active material A, peaks derived from the (010), (200), and (021) planes of orthorhombic LiMnO2 are confirmed, while peaks derived from the (110) and (210) planes of orthorhombic LiMnO2 are substantially not confirmed. That is, it can be said that the positive electrode active material A has a zigzag layered structure as a matrix structure and an α-NaFeO 2 type layered structure as a domain.
[0056] 2. Preparation of positive electrode active material B Positive electrode active material B: LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 A material having a composition represented by O2 and a layered rock salt structure was prepared.
[0057] 3. Carbon composite The positive electrode active material and acetylene black were weighed, and dry BM was carried out under the conditions shown in Table 2 below to carry out a composite treatment.
[0058] [Table 2]
[0059] 4.LiNbO3 coating The aqueous solution of LiNbO3 source and the positive electrode active material were weighed, mixed in a mortar, and dried to coat the surface of the positive electrode active material with LiNbO3. The coating weight was 10 mass%.
[0060] 5. Preparation of non-aqueous electrolyte battery (Comparative Examples 1 and 2) The carbon-composite positive electrode active material and PVdF as a binder were weighed out to a mass ratio of 95:5, and dispersed and mixed in N-methyl-2-pyrrolidone to obtain a slurry. The obtained slurry was applied onto an Al current collector foil, and vacuum dried overnight at 120°C to obtain a positive electrode. A coin cell (CR2032) was produced using the positive electrode, a non-aqueous electrolyte (TDDK-217 manufactured by Daikin Corporation), and a metallic lithium foil as a negative electrode. The charge / discharge characteristics of the produced coin cell were evaluated at an upper potential of 4.8V and a rate of 0.1C in a thermostatic chamber maintained at 25°C. The lower potential was 1.5V when the positive electrode active material A was used, and 3V when the positive electrode active material B was used. FIG. 3(A) shows the charge / discharge curves of a non-aqueous electrolyte battery (Comparative Example 1) when the positive electrode active material A was used.
[0061] 6. Preparation of all-solid-state battery (Comparative Example 3, Example 1) The positive electrode active material coated with LiNbO3, the sulfide solid electrolyte, PVdF as a binder, and VGCF as a conductive additive were weighed out in a mass ratio of 64.5:31.8:0.5:3.2, and dispersed and mixed in butyl butyrate to obtain a slurry. The obtained slurry was dried at 165°C to obtain a positive electrode composite. On the other hand, Li4Ti5O 12 The sulfide solid electrolyte, PVdF as a binder, and VGCF as a conductive assistant were weighed out to a mass ratio of 72.1:22.7:3.5:1.7, and dispersed and mixed in butyl butyrate to obtain a slurry. The obtained slurry was dried at 165°C to obtain a negative electrode composite. The positive electrode composite, the sulfide solid electrolyte, and the negative electrode composite were pressed together to obtain an all-solid-state battery. The charge-discharge characteristics of the obtained all-solid-state battery were evaluated at an upper potential of 4.8V and a 0.1C rate in a thermostatic chamber maintained at 25°C. The lower potential was set to -0.05V when the positive electrode active material A was used, and 1.45V when the positive electrode active material B was used. FIG. 3(B) shows the charge-discharge curve of the all-solid-state battery (Example 1) when the positive electrode active material A was used. The reversible capacity is different from that of FIG. 3(A), but this is due to the difference in the negative electrode.
[0062] 7. Capacity retention rate measurement Each battery was charged and discharged 30 times under the above conditions, and the capacity retention rate was measured based on the following formula. The results are shown in Table 3. Capacity retention rate = [(discharge capacity after 30 cycles) / (initial discharge capacity)] x 100
[0063] [Table 3]
[0064] The results shown in Table 3 reveal the following: (1) In Comparative Example 1, only a nonaqueous electrolyte was used as the electrolyte, and charging and discharging were performed at a high potential in order to fully utilize the performance of the positive electrode active material A. This is thought to have caused the electrolyte to gradually decompose during charging and discharging. As a result, the capacity retention rate after 30 cycles was significantly reduced. (2) In Comparative Example 2, it is considered that the use of the sulfide solid electrolyte and the positive electrode active material B caused the sulfide solid electrolyte and the positive electrode active material B to react with each other, which made it easy for a resistor to be formed. As a result, the capacity retention rate after 30 cycles was significantly reduced. (3) In Comparative Example 3, only a nonaqueous electrolyte was used as the electrolyte, and charging and discharging were performed at a high potential in order to fully utilize the performance of the positive electrode active material B. This is believed to have led to gradual decomposition of the electrolyte during charging and discharging. As a result, the capacity retention rate after 30 cycles was significantly reduced. (4) The capacity retention rate after 30 cycles was higher in Example 1 than in Comparative Examples 1 to 3. It is considered that the sulfide solid electrolyte is less likely to decompose even at a high potential, and that the positive electrode active material A has low reactivity with the sulfide solid electrolyte, and therefore the above-mentioned problems of decomposition of the electrolyte and reaction between the sulfide solid electrolyte and the positive electrode active material were less likely to occur.
[0065] As described above, a positive electrode for a lithium ion battery satisfying the following requirements (1) and (2) can suppress decomposition of the electrolyte and reaction between the electrolyte and the positive electrode active material, even in a lithium ion secondary battery used in a wide SOC range with a reversible capacity of 250 mAh / g or more, where the electrolyte is exposed to a high potential during charging and discharging, thereby improving the cycle characteristics of the battery. In addition, a sufficient discharge capacity can be obtained as a positive electrode.
[0066] (1) The electrolyte contains a sulfide solid electrolyte. (2) Li as the positive electrode active material x Mn y The composition is represented by the formula: O2 (0.95≦x≦1.05 and 0.95≦y≦1.05), and the composition includes a zigzag layered structure as a matrix structure and an α-NaFeO2 type layered structure as a domain. [Explanation of symbols]
[0067] 10 positive electrode 11 Cathode active material layer 12 Positive electrode current collector 20 Sulfide solid electrolyte layer 30 negative electrode 31 Negative electrode active material layer 32 Negative electrode current collector 100 Lithium-ion secondary battery
Claims
[Claim 1] A lithium ion secondary battery, A positive electrode and A sulfide solid electrolyte layer; A negative electrode; having The positive electrode is A sulfide solid electrolyte; A positive electrode active material, Li x Mn y O 2 (0.95≦x≦1.05 and 0.95≦y≦1.05), and having a zigzag layered structure as a matrix structure and α-NaFeO as a domain. 2 having a layered structure, Including, A protective layer containing a Li ion conductive oxide is formed on the surface of the positive electrode active material. Lithium-ion secondary battery.
Citation Information
Patent Citations
Lithium battery
JP1998064516A
Method of producing lithium manganese complex oxide
JP2001302245A
Lithium battery
JP2009170183A
Method for manufacturing coated active material
JP2012234648A
Positive electrode mixture
JP2017224474A